Designing anticipatory policies through the use of ICTs. Issue 1 (29th August 2018) - Capano, Giliberto; Pavan, Elena
Abstract: This paper seeks to achieve a better understanding of how and under what conditions current digital communication technologies can become an asset to the design of effective policies. In order to do so, we bridge two strands of reflection that have hitherto developed quite independently – i.e. policy design studies and researches on the use of information and communication technologies (ICTs) to reform the public sector. We start from the assumption that different governmental political and technical capacities shape different spaces for action and thus different types of policy design in which policy-makers can involve citizens via ICTs in three modes: co-design; design fine-tuning; crowdsourced policy design. According to this framework, we analyse three different 'revelatory case studies' in which ICTs have been employed by governments while designing policies: Iceland's recent experiment to redraft collectively its constitution; La Buona Scuola, the latest Italian public education law; and the Finnish Avoin Misteriö, a platform for crowdsourced legislation. By exploring the different modes in which ICTs have been integrated in the formulation of these three policies, we show that it is possible to disentangle different and more or less effective ways of exploiting ICTs' networking and communicative potential for designing successful public policies.